Evolution and the foundations of ethics : evolutionary perspectives on contemporary normative and metaethical theories - Mizzoni, John (Lexington Books, 2017)
This book outlines the rich array of work being done with evolution and ethics by biologists, zoologists, paleontologists, philosophers, theologians, psychologists, and political scientists. John Mizzoni argues that we can understand ethical elements more deeply through an evolutionary perspective and ten theories of ethics.